E-portfolios: an effective way to support constructive peer feedback in primary education - Iolie Nicolaidou (My University, 2011)
How can peer feedback be encouraged in primary education? Can e-portfolios provide a pedagogical strategy to support peer feedback for essay writing? Empirical studies on peer feedback as an instructional strategy to affect students’ writing showed that it can be valuable for increasing students’ writing performance [1]. E-portfolios invite feedback and comments from people they are shared with or shown to, such as teachers, peers or parents [2]. However, research on e-portfolios and peer feedback in primary education has mostly been anecdotal. This paper presents the findings of a yearlong study conducted in three 4th grade primary classes in Cyprus where both e-portfolios (n1=20) and paper-based portfolios (n2=23, n3=20) were implemented to help students document their progress and send feedback to peers on their essays. As there were no portfolio tools available in the Greek language, a generic, open source weblog tool was transformed and localized into Greek to be used as a digital portfolio tool. As the same thinking about purpose and pedagogy lies behind paper-based portfolios and e-portfolios [3], the three classes were treated as one sample. Students provided direct or indirect corrective feedback based on a feedback code sheet for nine essays included in their portfolios throughout the year. A portfolio artifact analysis focused on 514 student-essays and 2822 instances of peer feedback. Among the data sources were also students pre- and post-tests on writing performance administered prior to and at the end of portfolio implementation. Semi-structured, videotaped interviews were also conducted with nine students and two teachers to examine their perspectives on portfolios and peer feedback. The descriptive statistics of students’ peer feedback as this was reflected in the number of their comments showed that students provided more thorough peer feedback over time using portfolios and became gradually more capable of identifying their peers’ mistakes and of providing corrective feedback. A qualitative content analysis of the comments students received in their e-portfolios showed a gradual improvement, particularly evident in the first four months of portfolio implementation. During the first month, 90% of the comments students submitted were classified as “simple feedback” (providing one general comment and identifying one or two mistakes). Over four months this percentage dropped to 33%. Moreover, 64% of the students’ comments consisted of “constructive feedback” (providing at least one positive comment and more than three suggestions for improvement). Results also focused on the relationship between students’ writing performance and peer feedback over time. Findings from the qualitative analysis of students’ interviews showed that students valued peer feedback in their portfolios but also identified that it was not always correct. Findings from the qualitative analysis of teachers’ interviews showed that low-ability students sometimes failed to take corrections into consideration when they wrote a second draft of their work. This study provided evidence that e-portfolios and paper-based portfolios can support the development of students’ writing performance and peer feedback skills in the context of primary school essay writing. It also revealed some advantages of e-portfolios compared to paper-based portfolios, which included easier access to students’ work which, in turn, facilitated peer feedback, interactivity and communication. Instructional implications for portfolio implementation are also offered.
Keywords: E-Portfolios; Peer Feedback; Writing; Primary Education; Students’ Perceptions